Pengaruh Penambahan Kawat Bendrat Dan Fly Ash Terhadap Nilai Kuat Tekan Beton - Mahastie Sekar Arum; Abdul Basid; Djamaludin Djamaludin (JURNAL ILMIAH FAKULTAS TEKNIK, 2023)
Background: Concrete is the main structural component of a building and consists of sand, cement, broken stones, and water, with additional elements as needed. Water use in this study used 1% bend wire and 10% fly ash, 2% bend wire and 12% fly ash, and 3% bend wire and 16%. Method: In the abstract, the method used is the experimental method. Purpose: to to find out the effect of mixing bend wire and fly ash with various presentations on the strength of concrete press. Research Results: After the study, the concrete with the greatest pressure strength compared to other concrete was 3% bend wire concrete and 16% fly ash (BKFA 3) with a concrete pressure strength of 24.88 MPa. Conclusion: Therefore, this study can be said to be successful because Concrete with an additional variation of 3% bend wire and 16% flyash has a strong pressure value of 24.88 Mpa has a stronger pressure value higher than the plan's strong pressure, f'c of 22.83 MPa or K275.